HUBUNGAN OBESITAS DENGAN RANGE OF MOTION SENDI LUTUT REMAJA PADA SISWA SMP DI KOTA YOGYAKARTA - , ARINI GISKA SAFITRI, dr. Emy Huriyati M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : The prevalence of obesity is increasing every year. Besides to adults, obesity is also commonly found in children and adolescents. Obese people are at greater risk for experiencing limitations walking. Joints with Range of Motion (ROM) is limited are more likely to experience injury. Joint ROM is the result of the measurement may be carried out by the movement of the joints of the body. Obesity can reduce the value of the ROM so that limits the range of movement of the joints that may result in limited runs. Aim : To identify the relationship of obesity with the limitations of the knee joint ROM and the correlation with BMI values with knee joint ROM values in adolescent junior high school students in Yogyakarta. Method : This study was an observational study with cross-sectional design. Data weight, height, and knee joint ROM values obtained by direct measurement. The statistical test used is the Chi-square test and Spearman's test with SPSS software. Result : From 10 samples of obesity, 80% samples had knee joint ROM limitation on one leg. Sample of 56 obese, 96.4% had knee joint ROM limitation on both legs. Statistical tests to determine the relationship between obesity and knee joint ROM limitation on one foot is 0.000 (p <0:05). Relationship between obesity and knee joint ROM limitation on both feet is 0.000 (p <0.05). There is a negative correlation between BMI values with the value of the ROM of the knee joint, both on the right knee joint (Ï = 0.944) and the left knee joint (Ï = 0.951). Conclusion: There is a relationship between obesity and knee joint ROM limitation in adolescent junior high school students in Yogyakarta. BMI values were negatively correlated with the value of the knee joint ROM. The higher the BMI value, the smaller the value of the knee joint ROM.